Mass spectrometry: a textbook - Gross, Jürgen H. (Springer eBook Collection Chemistry and Materials Science, 2004)
Gas Phase Ion Chemistry -- Isotopes -- Instrumentation -- Electron Ionization -- Fragmentation of Organic Ions and Interpretation of EI Mass Spectra -- Chemical Ionization -- Field Ionization and Field Desorption -- Fast Atom Bombardment -- Matrix-Assisted Laser Desorption/Ionization -- Electrospray Ionization -- Hyphenated Methods.